Research methods for business : a skill-building approach - Sekaran, Uma; Bougie, Roger (Hoboken, NJ : John Wiley & Sons, Inc., 2019)
'Previous editions of this book have been used in various research methods courses with great success. For many years the book has helped thousands of my own students (undergraduate students, graduate students and executive students), as well as many more around the world, to carry out their research projects. The great strength of Research Methods for Business is that students find it clear, informal, easy to use and unintimidating. I have tried to maintain these strengths in this eighth edition'--
Uma Sekaran appears as the first named author on earlier editions.
Includes bibliographical references and index.
Keywords: Business -- Research -- Methodology